Hubungan Antara Profil Protein Populasi Vektor Wereng Hijau Nephotettix virescens dan Gejala Penularan Tungro pada Tanaman Padi - Senoaji, Wasis; Rahardjo, Bambang Tri; Tarno, Hagus (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Nephotettix virescens is the most effective vector for transmitting tungro disease to rice plants. Two different viral particles cause Tungro transmission. Disease control was often not anticipated in the field, especially when planting is asynchronous, that cause been detected lately. At the cellular level, vector interactions with viruses indicate vector proteins response to viral in the body of vector insects which involved in virus transmission in plants. This study aims to describe the relationship between the differentiation of N. virescens vector protein profiles on the types of tungro symptoms resulting from the transmission to develop techniques for early detection and control of the transmission process. The workflow of this study is screening on vector insects to obtain protein candidates thought to have a role in tungro transmission that had never been previously reported. The results of this study suggested that proteins with estimated molecular weights of 132, 73, and 49 kDa are candidates for proteins that can be used for screening purposes or virulent vector tracing as an early warning alternative to control tungro disease in endemic areas.